2011
DOI: 10.1007/s00125-011-2126-4
|View full text |Cite
|
Sign up to set email alerts
|

AMP-activated protein kinase is activated in adipose tissue of individuals with type 2 diabetes treated with metformin: a randomised glycaemia-controlled crossover study

Abstract: Aims/hypothesis The hypoglycaemic actions of metformin have been proposed to be mediated by hepatic AMP-activated protein kinase (AMPK). As the effects of metformin and the role of AMPK in adipose tissue remain poorly characterised, we examined the effect of metformin on AMPK activity in adipose tissue of individuals with type 2 diabetes in a randomised glycaemia-controlled crossover study. Methods Twenty men with type 2 diabetes (aged 50-70 years) treated with diet, metformin or sulfonylurea alone were recrui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 49 publications
4
53
1
3
Order By: Relevance
“…It has been known that the inhibitory effects of metformin on fatty acid metabolism occur via preferential AMPK-α 1 phosphorylation in rat muscle cells [55] . More recently, Boyle [56] found that metformin activates AMPK and reduces ACC protein levels in human adipose tissue in vivo. Our data indicated that rutaecarpine and metformin potentially act on the same pathway to regulate lipid metabolism.…”
Section: Ins2mentioning
confidence: 99%
“…It has been known that the inhibitory effects of metformin on fatty acid metabolism occur via preferential AMPK-α 1 phosphorylation in rat muscle cells [55] . More recently, Boyle [56] found that metformin activates AMPK and reduces ACC protein levels in human adipose tissue in vivo. Our data indicated that rutaecarpine and metformin potentially act on the same pathway to regulate lipid metabolism.…”
Section: Ins2mentioning
confidence: 99%
“…39 However, our results are not according to research made in 3T3-L1 adipocytes, in which metformin reduces ACC1 protein. 40 These differences could be due to the fact that the regulation of the metabolism of different tissues may differ. Together, our results show a slight beneficial effect of metformin on the restitution of intestinal lipid/lipoprotein homeostasis.…”
Section: (Fas) (F) Apolipoprotein A-iv (Apo A-iv) (G) Diacylglyceromentioning
confidence: 99%
“…Also of note, more of the insulin resistant than insulin sensitive patients enrolled in our study were on metformin therapy. However, the use of this drug has been shown to increase AMPK activity in adipose tissue ( 49 ). Thus, if anything, this would have made for higher rather than lower AMPK activity in the insulin resistant subjects.…”
Section: Nampt Protein Expression Is Decreased In Omental Fat Of Insumentioning
confidence: 99%